(untitled) (Research, Society and Development, 2022)
The present article is part of a research project carried out to identify the socio-environmental impacts, in an expanded perspective of the impacts produced by the construction of the centrality of Kilamba, Luanda, Angola. The centralities are a type of construction carried out in Angola from 2008, aiming to meet the population’s housing demand. They constitute a set of works that covered: Construction of houses, social facilities, including kindergartens, primary and secondary schools, health center, community parks, shopping areas and leisure areas. The methodology used was qualitative through the case study. The objective was to identify the impacts of the main stages of construction: planning, execution and operationalization.The study comprised, bibliographic survey, literature review, interviews, site visits, that was possible to identify the social, environmental, ecological and cultural impacts of each stage that compromise the life and development of the population and the ecological and environmental chains, responsible for the supply of ecosystem services, important for tackling global environmental problems, such as climate change and the occurrence of pandemics.